Second-order nonlinearity generation in alkali-glass-based optical fibers - Anuszkiewicz, Alicja; Kasztelanic, Rafał; Buczyński, Ryszard (Photonics Letters of Poland, 2025)
We analyzed the mechanism of alkali-ions migration taking part in obtaining the frozen ionic potential responsible for the creation of second-order nonlinearity in optical fibers made of silica and other oxide-based glasses. We confirmed that the presence of alkali ions in the oxide glass, together with a high χ(3) value, allows to obtain ionic potential, even though these ions are structural elements of glass rather than impurities. Creation of second-order susceptibility in glass is possible and, depending on alkali-ion concentration, χ(2) can be higher than for a silica-based fiber of the same geometry. Calculated χ(2) reached 0.58 pm/V, and the maximum value obtained for silica-based fiber for the same thermal poling conditions was only 0.33 pm/V. Full Text: PDF References U. Österberg and W. Margulis, "Experimental studies on efficient frequency doubling in glass optical fibers," Opt. Lett. 12(1), 57 (1987) CrossRef H. An and S. Fleming, "Creating second-order nonlinearity in pure synthetic silica optical fibers by thermal poling," Opt. Lett. 32(6), 832 (2007) CrossRef H. An and S. Fleming, "Second-order optical nonlinearity in thermally poled borosilicate glass," Appl. Phys. Lett. 89(18), 181111 (2006) CrossRef W. Margulis, O. Tarasenko, and N. Myrén, "Who needs a cathode? Creating a second-order nonlinearity by charging glass fiber with two anodes," Opt. Express 17(17), 15534 (2009) CrossRef F. De Lucia, D.W. Keefer, C. Corbari, and P.J.A. Sazio, "Thermal poling of silica optical fibers using liquid electrodes," Opt. Lett. 42(1), 69 (2017) CrossRef P. Kabaciński, T.M. Kardaś, Y. Stepanenko, and C. Radzewicz, "Nonlinear refractive index measurement by SPM-induced phase regression," Opt. Express 27(8), 11018 (2019) CrossRef A. Kudlinski, Y. Quiquempois, G. Martinelli, "Modeling of the χ(2) susceptibility time-evolution in thermally poled fused silica," Opt. Express 13(20), 8015 (2005) CrossRef A. Camara, O. Tarasenko, and W. Margulis, "Study of thermally poled fibers with a two-dimensional model," Opt. Express 22(15), 17700 (2014) CrossRef F. Bergmann et al., "Measuring the permittivity of fused silica with planar on-wafer structures up to 325 GHz," Appl. Phys. Lett. 124(7), 072902 (2024) CrossRef Corning Inc., "Datasheet for Corning Pyrex glass," Aug. 13, 2025. DirectLink B. Morova et al., "Fabrication and characterization of large numerical aperture, high-resolution optical fiber bundles based on high-contrast pairs of soft glasses for fluorescence imaging," Opt. Express 27(7), 9502 (2019) CrossRef R.W. Boyd, "The nonlinear optical susceptibility," in Nonlinear Optics, 3rd ed., Academic Press, 2008, 1-67. CrossRef